2020
DOI: 10.1177/0095327x20917166
|View full text |Cite
|
Sign up to set email alerts
|

Patriotism or Paychecks: Who Believes What About Why Soldiers Serve

Abstract: Although voluntary recruitment to the military is today the Western norm, we know little about citizens’ beliefs regarding service members’ reasons for joining. This article, reporting and analyzing the results of a nationally representative U.S. survey, rectifies this gap. We find that, despite the reality of market-based recruitment, many Americans continue to subscribe to an idealized image of service members as moved by self-sacrificing patriotism. This belief is most heavily concentrated among conservativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 33 publications
1
12
0
Order By: Relevance
“…Patriotism as a motive for choosing military service is constantly at the center of the discussion among researchers from different countries. Krebs & Ralston (2020) argues that many Americans continue to subscribe to an idealized image of service members as moved by self-sacrificing patriotism. A unique example of the manifestation of patriotism is the volunteer movement of Ukrainian citizens in the first years (2014)(2015) of the War in the East of Ukraine, called the "dobrobaty" (volunteer battalions) (Stasiuk, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Patriotism as a motive for choosing military service is constantly at the center of the discussion among researchers from different countries. Krebs & Ralston (2020) argues that many Americans continue to subscribe to an idealized image of service members as moved by self-sacrificing patriotism. A unique example of the manifestation of patriotism is the volunteer movement of Ukrainian citizens in the first years (2014)(2015) of the War in the East of Ukraine, called the "dobrobaty" (volunteer battalions) (Stasiuk, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Also described within the Krebs & Ralston (2020) article was the distinct difference in perceptions of patriotism by civilians and family members of service members and those in military service. In context, military members did not report patriotism as a predominant factor for joining the military; however, civilians and the family members of service members said patriotism was a principal reason people served (Krebs & Ralston, 2020). It is also important to note that few studies about patriotism in military service and its effects on military service can be generalized due to limited research.…”
Section: Patriotism As a Constructmentioning
confidence: 99%
“…A 2020 research article about patriotism in military service, not specific to LGBTQ+ veterans, suggested that patriotism is often not a significant reason people offer for rationalizing their service in the military (Krebs & Ralston, 2020). The article also discussed how patriotism was more of a factor for people enlisting in the military after the September 11, 2001 (09/11), terrorist attacks; more people reported patriotism as a reason to enlist.…”
Section: Patriotism As a Constructmentioning
confidence: 99%
“…People who trust an institution are also more likely to defer to its leading members' judgment and to wish to grant that institution autonomy and to minimize intrusive oversight of it. Political liberals conversely would be less deferential to the military and more sensitive to officers' intrusion into policy debate (Krebs and Ralston 2020).…”
Section: Finding #2: In Civil-military Relations Too Politics Trumps Principlementioning
confidence: 99%